IMPLEMENTASI PENDIDIKAN MORAL PANCASILA KEPADA SISWA SEBAGAI NILAI BUDI PEKERTI DI MTS. ULUMUL QUR’AN MEDAN - Aulia, Nazlah; Nova Ramadhani, Kania; Silverius Sinaga, Reylan; Yunita, Sri (Inspiratif Pendidikan, 2023)
The mini research assignment for group 7 from class B PPKn 2023 is entitled "Implementation of Pancasila Moral Education for Students as a Value of Ethics in Mts. Ulumul Qur'an". This mini research examines how the application of Pancasila values ​​and morals to Mts.Ulumul Qur'an students. This study aims to determine the process of implementing moral values ​​in Mts. Ulumul Qur'an and to find out the role of schools in efforts to instill moral values ​​for students at Mts. Ulumul Qur'an. Where in the application in everyday life students interact both among friends and older people are not good at showing attitudes that are in accordance with the implementation of the values ​​and morals contained in Pancasila. Which in Pancasila there are values ​​that form the basis of behavior in life. This mini research uses qualitative methods with a realist ethnographic design, namely research that explores the phenomenon under study, by studying documents, or interviews, to look for hidden meanings, stories that are not clear, something that has multiple interpretations, implied connotations, and voices that are not voiced. This research is expressed with observations to test or confirm theories and assumptions. The data collection instruments included observation, interviews, distributing questionnaires, literature study, and documentation. This mini research resulted in an understanding of the inculcation of Pancasila values ​​and morals in students so that they are better for the future.